Magnetic structures of R5Ni2In4 and R11Ni4In9 (R = Tb and Ho): strong hierarchy in the temperature dependence of the magnetic ordering in the multiple rare-earth sublattices. (9th November 2015) - Ritter, C; Provino, A; Manfrinetti, P; Pecharsky, V K; Gschneidner, K A; Dhar, S K
Abstract: The magnetic properties and magnetic structures of the R 5 Ni2 In4 and the microfibrous R 11 Ni4 In9 compounds with R = Tb and Ho have been examined using magnetization, heat capacity, and neutron diffraction data. Rare earth atoms occupy three and five symmetrically inequivalent rare earth sites in R 5 Ni2 In4 and R 11 Ni4 In9 compounds, respectively. As a result of the intra- and inter-magnetic sublattice interactions, the magnetic exchange interactions are different for various rare earth sites; this leads to a cascade of magnetic transitions with a strong hierarchy in the temperature dependence of the magnetic orderings. A transition at T C = 125 K in Tb5 Ni2 In4 [ κ 1 = (0, 0, 0)] leads to a ferro/ferrimagnetic order where the magnetic ordering in one of the three R -sublattices leads to the ordering of another one; the third sublattice stays non-magnetic. New magnetic Bragg peaks appearing below T N = 20 K can be indexed with the incommensurate magnetic propagation vector κ 2 = (0, 0.636, ½); at T N = 20 K a cycloidal spin order, which acts mostly upon the third R -sublattice, occurs. Ho5 Ni2 In4 establishes first antiferromagnetism [ κ = (0, 0, 0)] at T N = 31 K on two R -sublattices; then the system becomes ferro/ferrimagnetic at T C = 25 K with the third sublattice ordering as well. Tb11 Ni4 In9 has three magnetic transitions at T C = 135 K, T N1 = 35 K and at T N2 = 20 K; they are respectively coupled to the appearance of different propagation vectors [ κ 1 = (0, 0, 0), κ 2 = (0, 0, ½), κ 3 = (0, 1, ½)], which themselves are operating differently on the five different R -sublattices. Two sublattices remain mostly ferromagnetic down to lowest temperature while the three others are predominantly coupled antiferromagnetically. In Ho11 Ni4 In9 a purely antiferromagnetic order, described by four different magnetic propagation vectors [ κ 1 = (0, 0.62, 0), κ 2 = (0, 1, 0), κ 3 = (0, 0, ½), κ 4 = (0, 1, ½)], succeedingly includes all five different sublattices on cooling through transitions at T N1 = 22 K, T N2 = 12 K, T N3 = 8 K and T N4 = 7 K. The strength of the magnetic interactions of the different sublattices can be linked to structural details for both R 5 Ni2 In4 and R 11 Ni4 In9 compounds.